PENDIDIKAN DAN LATIHAN AKUNTANSI BAGI PELAJAR DAN MAHASISWA MELALUI PPUPIK PUSAT PELATIHAN AKUNTANSI UNIVERSITAS PGRI PALEMBANG - Zahruddin Zahruddin (Universitas Sebelas Maret, 2018)
Accounting education and training for students and college through PPUPIK,target this Accounting Training Center at the University of Palembang PGRI have 4,there are Senior high school / Islamic School students, vocational students, college and the general public. Accounting training is implemented in theory and practice, both accounting and computer accounting. The recognition system has been carried out byinvolving college of Edu Accounting Ambassadors and Accounting Education study program by visiting schools and campuses in Palembang to promote and / or establish cooperation. The activities were also published in the mass media, online and newspapers. The implementation of the activities that have been done with two classes, morning study class at 08.00 a.m- 12.00 a.m., afternoon study class is 12.00 a.m- 16.00 p.m. Accounting training conducted is divided into 4 classes, there are service company accounting, trading company accounting, manufacturing accounting and computer accounting (MYOB and Accurate). In phase 1 (February - March 2018) there were 149 participants from Senior high school, vocational School and Islamic School students, on phase 2 (May - June 2018) the participants were students from various universities totaling 149 people and on phase 3 (August - September 2018) the participants were 50 Senior high school, vocational School and Islamic School students. After studying 12-16 meetings, the final examination is conducted for those who have passed the certificate given. For teacher, besides the lecturer in Accounting Education Study Program and lecturer in Accounting Study ProgramUniversity of PGRI Palembang, and also involves brainy alumni . Teachers who come from partners are Prospect accounting courses. Guest lecturers are invited to public lectures and supplements.Keywords: Accounting, Training, Theory and Practice